Oracle data warehousing and business intelligence solutions - Stackowiak, Robert (Wiley ; John Wiley [distributor], 2007)
Up-to-date, comprehensive coverage of the Oracle database and business intelligence tools. Data warehouses are the core technology that businesses use to capture, store, and analyze vast amounts of business data, and Oracle has emerged as the leading database platform.